Workshop "Promoting the Digital Transformation in Higher Education through the Building of a Cohesive Network for Collaboration and Transfer of Knowledge and Pedagogical Innovations" - Monova-Zheleva, Mariya; Zhelev, Yanislav (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2024)
The seminar " Promoting the Digital Transformation in Higher Education through the Building of a Cohesive Network for Collaboration and Transfer of Knowledge and Pedagogical Innovations " presents the approach and concept developed by seven organisations from Spain, Bulgaria, France, Italy andPortugal in the framework of international project European Network in D-Flexible Teaching (ENID-Teach), funded by the European Commission through theErasmus + programme, KA220-HED - Cooperation Partnerships in Higher Education, aiming to foster the intra- and inter-university cooperation in providing a coherent and stable response to the urgent need of measures and adjustments related to the digital shift and the provision of quality digital university education informed by modern technology and innovative pedagogy with greater commitment to social inclusion and equality.
Keywords: Digital Education; Flexible Methodologies; Microlearning Methodology; NOOCs /Nano Open; Massive and Online Courses/; Higher Education